MENGUBAH POLA PIKIR ORANGTUA DENGAN HYPNOTHERAPY : Strategi Parenting Efektif - Nur Hermatasiyah; Fitri Husaibatul Khairat Hsb; Sarah Fadzilah; Savera Amelia Fatihah; Tiara Ayu Rachmadi (Education and Community Service Journal (EduServe), 2025)
Parenting plays a fundamental role in determining children's success, yet most parents still rely on past experiences, social norms, religion and local culture as the basis for parenting practices. This condition often causes a gap between parents' expectations and children's behavior, so a new, more effective approach is needed. This research aims to change the mindset of parents through hypnotherapy-based parenting strategies, so that they are able to understand the causes of children's behavioral problems while managing the emotional aspects of parenting. The activity was carried out through a socialization program in Kayu Bongkok Village by involving student collaboration as facilitators and the community as active participants. The method used was parenting education and training with hypnotherapy techniques designed to improve understanding, skills, and the ability to manage stress and anxiety in parenting. The results showed a significant increase in parents' knowledge and skills, especially in the application of positive parenting in the family environment. Overall, this activity proved to be able to empower the people of Kayu Bongkok Village by fostering awareness, a spirit of change, and strengthening parenting in accordance with the demands of the times.